2016
DOI: 10.1007/s12034-016-1314-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and non-isothermal degradation kinetics of novel poly(mono ethylene glycol dimethacrylate-co-4-aminobenzoate)

Abstract: Synthesis of a novel co-polymer made by the addition polymerisation between MEGDMA and 4-AB by aza-Michael addition (AMA) polymerisation method is a fascinating field of research. The present investigation yielded a hazardous metal catalyst-free and toxic solvent-free methodology. The AMA polymerisation was carried out at five different [M 1 /M 2 ] values under N 2 atmosphere at 100 • C for 2 h. Thus, obtained co-polymer was characterized by Fourier transform infrared spectroscopy, UV-visible reflectance spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The decomposition temperature ( T d ) of PCL was found to be increased while increasing the heating rate from 10 to 30°C/min. The similar trend was observed for initial and final decomposition temperatures of PCL with the rising heating rate . The major weight loss accompanied with the breaking of PCL backbone started around 270°C for the heating rate of 10°C/min.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The decomposition temperature ( T d ) of PCL was found to be increased while increasing the heating rate from 10 to 30°C/min. The similar trend was observed for initial and final decomposition temperatures of PCL with the rising heating rate . The major weight loss accompanied with the breaking of PCL backbone started around 270°C for the heating rate of 10°C/min.…”
Section: Resultssupporting
confidence: 80%
“…Hence, it was concluded that T d is increased proportionally with the increasing heating rates. The E a for the thermal degradation of PCL was calculated by the well‐known non‐isothermal kinetics models . In FWO model, the E a value was estimated as135.8 kJ mol −1 from the plot of lnβ versus 1,000/ T d as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All the thermograms showed three‐step degradation processes. It was found that the degradation steps interestingly shift toward higher temperature with the increasing heating rates . It was further confirmed by DTG thermograms as shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…where, W o refers to the initial weight of the sample, W t is the weight at any specified temperature, and W f is the weight of the sample at the end of the process. In FWO method , the measurement of temperature is based on the fixed value, α at different heating rates. The E a is measured without knowing the reaction mechanism and order.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation